The Influence of Product Quality and Price on Consumer Satisfaction of Brownies Prima Products in East Jakarta - Arif Budiman; Sarwani; Dian Ferriswara (International journal of technology and education research, 2026)
This study aims to analyze the effect of product quality and price on customer satisfaction of Brownies Prima consumers in East Jakarta. The increasing competition in the food industry requires businesses to improve product quality and implement appropriate pricing strategies to maintain customer satisfaction. This study employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 100 Brownies Prima consumers selected using purposive sampling. The data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics. The results showed that product quality has a positive and significant effect on customer satisfaction, with a regression coefficient of 0.513, t-value of 10.501, and significance value of 0.000. Price also has a positive and significant effect on customer satisfaction, with a regression coefficient of 0.453, t-value of 9.026, and significance value of 0.000. Furthermore, the F-test results indicate that product quality and price simultaneously have a significant effect on customer satisfaction, with an F-value of 86.421 and a significance value of 0.000. The coefficient of determination shows that product quality and price explain 64.1% of the variation in customer satisfaction. This study concludes that improving product quality and implementing appropriate pricing strategies are important factors in increasing customer satisfaction among Brownies Prima consumers. The findings provide practical implications for businesses in developing strategies to maintain customer loyalty and competitiveness in the food industry.